GeV laser-plasma electron acceleration in a cm-scale capillary waveguide - Nakamura, K; Tóth, C; Nagler, B; Geddes, C; Schroeder, C; Esarey, E; Leemans, W; Gonsalves, A; Hooker, S (Optical Society of America, 2006)
33 mm plasma channels produced in a gas-filled capillary discharge and 40 TW, 40 fs laser pulses were used to produce GeV electron beams in a multi-table-top setup. © 2006 Optical Society of America.